(untitled) (Boulder, Colorado, 1982)
This book introduce the agricultural revolution. Technology transfer and the commerciallization of India agriculture. Alternate routes to agrarian change and the responsibility of research...
Keywords: Đổi mới nông nghiệp,Agricultural innovations; Hội nghị,Congresses; Châu Á,Asia